Assessing cultural ecosystem services of a large marine protected area through social media photographs. (15th June 2019) - Retka, Jared; Jepson, Paul; Ladle, Richard J.; Malhado, Ana C.M.; Vieira, Felipe A.S.; Normande, Iran C.; Souza, Carolina N.; Bragagnolo, Chiara; Correia, Ricardo A
Abstract: Cultural ecosystem services (CES) are defined as the non-material benefits that arise from human-ecosystem relationships. Such benefits contribute to quality of life and positive sentiment towards protected areas but are difficult to quantify, especially at large spatial scales. Building on recent studies, we assess CES in Brazil's largest marine protected area (MPA) using user-contributed georeferenced photographs from a popular image- and video-hosting website. In total, we assessed 1, 984 photographs taken by 207 users between 2010 and 2016. The most represented CES categories were landscape appreciation and social recreation, clearly reflecting the obvious attractions of this tropical beach location. Artistic/cultural expressions and appreciation, and nature appreciation where also highly represented, though no photographs depicting educational engagements or scientific research were identified. Engagements with CES had clear spatial and temporal patterns relating to user behaviour and reflecting the biophysical and infrastructural characteristics of different sites within this MPA. The broad spatial coverage and high spatio-temporal resolution of the data makes this approach ideal for identifying CES hotspots/coldspots and, despite limitations, holds great potential to monitor the impact of management interventions on CES provision. Our study highlights how the analysis of high volumes of digital photographs extends the methodological tool-box available to researchers and provides a powerful new means to quantify and map CES at broad spatial scales. Highlights: We used social media photos to assess engagements with the largest MPA in Brazil. Most photos represented landscape appreciation and social recreation situations. Higher photo densities were related to the availability of visitor infrastructure. Peaks of user engagement occurred during popular events and travel months. Social media has potential to monitor temporal and spatial engagements with MPAs.